2009
DOI: 10.1517/14740330903418430
|View full text |Cite
|
Sign up to set email alerts
|

Best practice guidelines for the management of adverse events associated with amphotericin B lipid complex

Abstract: Amphotericin B lipid complex represents a valuable therapeutic option in the treatment of fungal infections but improved strategies for the management of infusion-related adverse events are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Several combinations of premedication drugs were used including intravenous rapid acting corticosteroids alone; steroids and paracetamol; steroids, paracetamol, and antihistamines all together. Recent studies have highlighted the importance of premedication regimens combined with a reduction in the infusion rate to minimize, or even prevent, the onset of IRRs, which are based on the administration of systemic corticosteroids, paracetamol, with or without chlorphenamine ( 8 ). The reported incidence of IRRs with ABLC has ranged between 2 and 23% in several studies ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several combinations of premedication drugs were used including intravenous rapid acting corticosteroids alone; steroids and paracetamol; steroids, paracetamol, and antihistamines all together. Recent studies have highlighted the importance of premedication regimens combined with a reduction in the infusion rate to minimize, or even prevent, the onset of IRRs, which are based on the administration of systemic corticosteroids, paracetamol, with or without chlorphenamine ( 8 ). The reported incidence of IRRs with ABLC has ranged between 2 and 23% in several studies ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was a considerable heterogeneity among the studies, and the major conclusion was that they were comparable except for higher IRRs with ABLC compared to L-AMB ( 7 ). In this respect, Craddock et al ( 8 ) showed a marked decrease in IRRs reaction with ABLC while using premedications along with slow infusion rate, and even recommended a therapeutic algorithm that helps decreasing the rate of IRRs with minimal steroid use ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to commencing therapy, a test dose is recommended to ensure the patient does not experience a severe hypersensitivity reaction . Pre‐treatment with hydrocortisone and chlorphenamine appears to reduce the incidence of infusion‐related effects . Renal function should be monitored daily on initiation of therapy with amphotericin B, meaning that initiation of therapy may be challenging in the OPAT setting, and a period of hospital admission may be required to initiate therapy.…”
Section: Antifungal Agents Suitable For Opatmentioning
confidence: 99%
“…Mantarların membranına spesifik olup hücre zarındaki ergosterole bağlanıp permeabilite ve transport fonksiyonlarını bozarak fungusit etki gösterir. Oral absorbsiyonu düşük olup, intravenöz olarak kullanılmaktadır [16]. Fakat amfoterisin B' nin nefrotoksisite gibi ağır yan etkileri mevcut olup, vorikonazol gibi daha az yan etkiye sahip yeni antifungal ajanlar geliştirilmişitir [17].…”
Section: Tedaviunclassified